Preparation and Self-Cleaning Performance of High-Strength Double-Layer PVDF-PVC-Nano-Graphite/PVDF-PVC Super-Hydrophobic Composite Membrane - Dashuai Zhang; Shishu Sun; Yan Zhang; Xiaopeng Zhang; Chen Li; Tianyi Sun; Linhua Zhu; Zaifeng Shi (Molecules, 2023)
The double-layer PVDF-PVC (D-PP/PP) super-hydrophobic composite membrane was prepared by the coating immersion phase separation method to enhance the mechanical properties of the composite membrane. The D-PP/PP super-hydrophobic membrane was prepared using the casting solution concentration of 12 wt% PVDF-PVC composite membrane as basement and 4% casting of PVDF-PVC coating. The contact angle of the D-PP/PP membrane was 150.4 ± 0.3°, and the scanning electron microscope showed that the surface of the D-PP/PP membrane was covered by a cross-linked micro–nano microsphere. The mechanical properties showed that the maximum tensile force of the D-PP/PP composite membrane was 2.34 N, which was 19.4% higher than that of PVDF-PVC (1.96 N). Nano-graphite was added to the coating layer in the experiment. The prepared double-layer PVDF-PVC-nano-graphite/PVDF-PVC (D-PPG/PP) composite membrane reached 153.7 ± 0.5°, the contact angle increasing by 3.3°. The SEM comparison showed that the D-PPG/PP composite membrane had a more obvious micro–nano level microsphere layer. The mechanical properties are also superior. By preparing the D-PP/PP membrane, the mechanical properties of the membrane were improved, and the super-hydrophobic property of the coating was also obtained. At the same time, it was found that adding nano-graphite to the coating layer can better improve the hydrophobic, mechanical, and self-cleaning properties of the D-PP/PP composite membrane.